Analysis of TCRβ and TCRγ genes in Chinese alligator provides insights into the evolution of TCR genes in jawed vertebrates. (August 2018) - Wang, Xifeng; Wang, Peng; Wang, Renping; Wang, Chaolin; Bai, Jianhui; Ke, Cuncun; Yu, Di; Li, Kongpan; Ma, Yonghe; Han, Haitang; Zhao, Yaofeng; Zhou, Xin; et al.
Abstract: All jawed vertebrates have four T cell receptor (TCR) chains that are expressed by thymus-derived lymphocytes and play a major role in animal immune defence. However, few studies have investigated the TCR chains of crocodilians compared with those of birds and mammals, despite their key evolutionary position linking amphibians, reptiles, birds and mammals. Here, employing an Alligator sinensis genomic bacterial artificial chromosome (BAC) library and available genome data, we characterized the genomic organization, evolution and expression of TRB and TRG loci in Alligator sinensis . According to the sequencing data, the Alligator sinensis TRB locus spans approximately 500 Kb of genomic DNA containing two D-J-C clusters and 43 V gene segments and is organized as Vβ(39) -pJβ1-pCβ1-pDβ1-Dβ2- Jβ2(12) -Cβ2-Vβ(4), whereas the TRG locus spans 115 Kb of DNA genomic sequence consisting of 18 V gene segments, nine J gene segments and one C gene segment and is organized in a classical translocon pattern as Vγ(18) –Jγ(9) -Cγ. Moreover, syntenic analysis of TRB and TRG chain loci suggested a high degree of conserved synteny in the genomic regions across mammals, birds and Alligator sinensis. By analysing the cloned TRB / TRG cDNA, we identified the usage pattern of V families in the expressed TRB and TRG . An analysis of the junctions of the recombined VJ revealed the presence of N and P nucleotides in both expressed TRB and TRG sequences. Phylogenetic analysis revealed that TRB and TRG loci possess distinct evolutionary patterns. Most Alligator sinensis V subgroups have closely related orthologues in chicken and duck, and a small number of Alligator sinensis V subgroups have orthologues in mammals, which supports the hypothesis that crocodiles are the closest relatives of birds and mammals. Collectively, these data provide insights into TCR gene evolution in vertebrates and improve our understanding of the Alligator sinensis immune system. Highlights: First characterization of the genomic organization of the TCRB and TCRG locus of Chinese alligator. Identified the usage of V families, the N and P nucleotides and the length of CDR3 in the expressed TRB and TRG. Phylogenetic analysis revealed that TRB and TRG loci possess different evolutionary patterns.